FOCUS ON PRESENT MOMENT FOR YOUR SLEEP: MINDFULNESS PROMOTES MID-LIFE ADULTS' SLEEP HEALTH. (20th December 2022) - Smith, Claire; Mu, Christina; Venetto, Angelina; Khan, Arooj; Lee, Soomi
Abstract: Sleep health during midlife sets the stage for health over the lifespan. Mindfulness, or present-moment awareness and attention, is shown to benefit sleep, yet mechanisms explaining these benefits are missing. Applying self-regulation theory, we test affective and cognitivemechanisms linking mindfulness to quantitative and qualitative sleep health. Across two independent samples of nurses (N1=60; N2=84), ecological momentary assessment (measuring mindfulness, sleep quality and sufficiency, positive and negative affect, and rumination) and actigraphy (sleep duration and wake-after-sleep-onset [WASO]) were collected over fourteen days. Multilevel mediation revealed that, between people, mindfulness generally associated with better sleep quality and sufficiency, mediated by lower rumination and negative affect. Within people, daily mindfulness associated with better sleep sufficiency, mediated by higher positive affect. Our findings position mindfulness as an emotional and cognitive self-regulation strategy that promotes midlife adults' qualitative – but not quantitative -- sleep health. Results may inform health interventions during this pivotal life stage.